The potential risks and impact of the start of the 2015–2016 influenza season in the WHO European Region: a rapid risk assessment. Issue 4 (14th May 2016) - Tjon‐Kon‐Fat, Raïssa; Meerhoff, Tamara; Nikisins, Sergejs; Pires, João; Pereyaslov, Dmitriy; Gross, Diane; Brown, Caroline; ,
Abstract : Background: Countries in the World Health Organization (WHO) European Region are reporting more severe influenza activity in the 2015–2016 season compared to previous seasons. Objectives: To conduct a rapid risk assessment to provide interim information on the severity of the current influenza season. Methods: Using the WHO manual for rapid risk assessment of acute public health events and surveillance data available from Flu News Europe, an assessment of the current influenza season from 28 September 2015 (week 40/2015) up to 31 January 2016 (week 04/2016) was made compared with the four previous seasons. Results: The current influenza season started around week 51/2015 with higher influenza activity reported in Eastern Europe compared to Western Europe. There is a strong predominance of influenza A(H1N1)pdm09 compared to previous seasons, but the virus is antigenically similar to the strain included in the seasonal influenza vaccine. Compared to the 2014/2015 season, there was a rapid increase in the number of severe cases in Eastern European countries with the majority of such cases occurring among adults aged <65 years. Conclusions: The current influenza season is characterized by an early start in Eastern European countries, with indications of a more severe season. Currently circulating influenza A(H1N1)pdm09 viruses are antigenically similar to those included in the seasonal influenza vaccine, and the vaccine is expected to be effective. Authorities should provide information to the public and health providers about the current influenza season, recommendations for the treatment of severe disease and effective public health measures to prevent influenza transmission.